Meningkatkan Kualitas Laba Melalui Corporate Governance - Prastyanti, Tessa Rachel; Indarti, MG Kentris; Widiatmoko, Jacobus (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to examine the effect of independent commissioners, audit committees, and managerial ownership on earnings quality. This study uses three control variables, namely firm size, profitability, and leverage. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Sampling using purposive sampling technique produces 182 data. The results obtained indicate that managerial ownership has a significant positive effect on earnings quality. Ownership of shares owned by directors is considered capable of providing oversight of performance between agents and management. In contrast, independent commissioners and audit committees have no effect on earnings quality. This is because the supervision carried out by independent commissioners and audit committees is considered less than optimal. For the variable firm size, profitability, and leverage have a significant positive effect on earnings quality.